Twitter for dummies - Fitton, Laura (Wiley Publishing, 2009)
Twitter can boost your business and marketing efforts, and this guide shows you how Twitter, the simple-to-use microblogging service, offers immense benefits for businesses and organizations. In this easy-to-follow guide, you'll discover how to get set up on Twitter, build a follower list, and find a voice for your tweets